Morphologica characterization of 39 lulo (Solanum quitoense Lam.) genotypes proceeding from the Nariño´s University collection - Riascos, Marcela; Santacruz, Adriana; Lagos B, Tulio; Checa C, Oscar (Revista de Ciencias Agrícolas, 2012)
The 39 genotypes of the lulo collection were characterized morphologically (Solanum qui- toense Lam.) at Buesaco (Nariño Department) at 1.959 meters above sea level. The samples came from the departments of Cauca, Nariño, Valle del Cauca, Risaralda and Antioquia. The analysis of Principal Components indicated that the first five factors explained 80,39% of the total variation evaluated, and the hierarchical classification grouped in five classes, revealed a high contribution of the variables related to the fruit. The analysis of the Multiple Correspondence indicated that the first five factors explained 51,27% of the total variation. The characteristics that most contributed were the purple petiole color, the color green of pubescence of stem, the velvety pubescence of the stem, the purple pubescence of the leaf, the presence of spines on the stem and leaves. In the classification analysis for qualitative attributes four groups were identified in which the variability was concentrated in higher proportions in the descriptors related to fruit and thorns. The 39 introductions of lulo were morphologically characterized according to the18 quantitative variables and the 18 qualita- tive variables evaluated. The results and the knowledge obtained from this research have paramount importance for improving the fruit (Lulo) in terms of agronomic and organolep- tic properties.